Weekly streamflow forecasting of Rhine river based on machine learning approaches - Zohreh Sheikh Khozani; Elimar Precht; Monica Ionita (Natural Hazards, 2025)
The Rhine River is a vital waterway in Europe, crucial for navigation, hydropower generation, and ecosystem health. Thus, accurately forecasting its streamflow is essential for effective water resource management. This study explored the utilization of several Machine Learning (ML) techniques including Multi-layer Perceptron (MLP), Support Vector Regression (SVR), K-Nearest Neighbor (KNN), and eXtreme Gradient Boosting (XGBoost), for forecasting weekly streamflow for the Rhine River. Meteorological data (e.g., precipitation, temperature, vapor pressure deficit) collected from meteorological stations situated on the main river course (i.e., Mannheim and Worms) spanning from 2013 to 2023 were used as predictors. Two scenarios were considered for predicting weekly streamflow according to the results of the best input combination. According to the results streamflow is most significantly predicted by precipitation, vapor pressure, and relative humidity, while average and maximum temperatures play a smaller role. Various quantitative and visually-oriented evaluation metrics were employed to validate and compare the performance of the proposed models. It found that the XGBoost outperformed than other algorithms in prediction of weekly streamflow in Rhine River. Overall, weekly streamflow forecasting for the Rhine River is crucial for effective water resource management, navigation, hydropower generation, flood control, and ecosystem health. By providing timely insights into flow variations and identifying the optimal predictors, weekly forecasts empower stakeholders to make informed decisions and ensure the Rhine’s continued sustainability.

Making water flow: a comparison of the hydrodynamic characteristics of 12 different benthic biological flumes - Per R. Jonsson; Luca A. van Duren; Muriel Amielh; Ragnhild Asmus; Rebecca J. Aspden; Darius Daunys; Michael Friedrichs; Patrick L. Friend; Frédéric Olivier; Nick Pope; Elimar Precht; Pierre-Guy Sauriau; et al. (Aquatic Ecology, 2006)

Near-bottom performance of the Acoustic Doppler Velocimeter (ADV) – a comparative study - Elimar Precht; Felix Janssen; Markus Huettel (Aquatic Ecology, 2006)

Oxygen dynamics in permeable sediments with wave‐driven pore water exchange - Elimar Precht; Ulrich Franke; Lubos Polerecky; Markus Huettel (Limnology and Oceanography, 2004)
The effects of advective pore water exchange driven by shallow water waves on the oxygen distribution in a permeable (k = 3.3 x 10 −12 to 4.9 x 10 −11 m 2 ) natural sediment were studied with a planar oxygen optode in a wave tank. Our experiments demonstrate that pore water flow driven by the interaction of sediment topography and oscillating boundary flow changes the spatial and temporal oxygen distribution in the upper sediment layer. Oxygenated water intruding in the ripple troughs and deep anoxic pore water drawn to the surface under the ripple crests create an undulating oxic‐anoxic boundary within the upper sediment layer, mirroring the topographical features of the sediment bed. Anoxic upwelling zones under ripple crests can separate the oxic sediment areas of neighboring ripple troughs with steep horizontal oxygen concentration gradients. The optode showed that migrating wave ripples are trailed by their pore water flow field, alternately exposing sediment volumes to oxic and anoxic pore water, which can be a mechanism for remobilizing particulate oxidized metal precipitates and for promoting coupled nitrification‐denitrification. More rapid ripple migration (experimental threshold ~20 cm h −1 ) produces a continuous oxic surface layer that inhibits the release of reduced substances from the bed, which under slowly moving ripples is possible through the anoxic vertical upwelling zones. Swift, dramatic changes in oxygen concentration in the upper layers of permeable seabeds because of surface gravity waves require that sediment‐dwelling organisms are tolerant to anoxia or highly mobile and enhance organic matter mineralization.

Advective pore‐water exchange driven by surface gravity waves and its ecological implications - Elimar Precht; Markus Huettel (Limnology and Oceanography, 2003)
The effects of surface gravity waves on pore‐water release from permeable sediment (k = 1.3–1.8 × 10 −11 m 2 ) in shallow water were studied in a wave tank. Our tracer experiments demonstrated that shallow‐water waves can increase fluid exchange between sandy sediment and overlying water 50‐fold, relative to the exchange by molecular diffusion. The main driving force for this increased exchange are the pressure gradients generated by the interaction of oscillating boundary flows and sediment wave ripples. These gradients produce a pore‐water flow field, with a regular pattern of intrusion and release zones, that migrates with ripple propagation. The ensuing topography‐related filtering rates in the wave tank ranged from 60 to 590 L m −2 d −1 and exceeded the solute exchange rates caused by hydrostatic wave pumping (38 L m −2 d −1 ) and initial molecular diffusion (corresponding to 10–12 L m −2 d −1 ). Wave‐induced filtration is ecologically relevant because permeable sandy sediments are very abundant on the continental margins and can be converted into effective filter systems, which suggests that these sediments are sites for rapid mineralization and recycling. We propose that the wave influenced continental shelf may be subdivided into two zones: a shallow zone (water depth

Hydrodynamical impact on biogeochemical processes in aquatic sediments - Markus Huettel; Hans Røy; Elimar Precht; Sandra Ehrenhauss (Hydrobiologia, 2003)